Telaah Konsep Pendidikan Islam dalam Perspektif Asy-Syekh Az-Zarnuji - Mahrus Hadi; Mar Syahid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2023)
So far, education is considered a failure, not just not meeting job standards. The bigger problem is that our education is not used to producing satisfactory graduates with noble character. The ancient nations that were destroyed by God, not because they did not master science and technology or were not smart, but because they had wrong intentions, methods, and did not know what the ultimate goal was and worst of all, they did not practice their knowledge, therefore they did not have good morals. . Is it not true that people who take a wrong step or do not know the procedure in seeking educational knowledge are very bad. As a religion that prioritizes education, throughout the life of Islam, there have been many thinkers who have contributed their thoughts in the field of educational concepts in particular, as well as from various other fields. Ibn Sina, Al-Qobisi, Ibn Taimiyah, Maskawaih, Al-Ghazali, Kh Imam Zarkasi, Az-Zarnuji who contributed their thoughts to the perfection and advancement of the concept of Islamic education based on the Qur'an and the Sunnah of the Prophet. The views of Islamic education thinkers or experts, especially Sheikh Az-Zarnuji in this study, have been brought back for joint study, so that we can use them as guidelines or guidelines and further study of systems or methods of educational concepts based on The Qur'an and the Sunnah of the Prophet SAW. This researcher seeks to express Az-Zarnuji's thoughts in the book Ta'limul Muta'alim in the form of messages about the concept of Islamic education. The type of research used is Library Research with a qualitative approach, based on that data is taken from the original source and is supported by related sources. The data collection method uses documentation. Data analysis techniques with three components: data reduction (data reduction), data presentation (data display) and drawing and verifying conclusions. Following the formulation of Miles and Huberman, while the method of checking the validity of the data with five components; (1) triangulation, (2) checking the truth of information, (3) munaqosah, (4) analysis of negative cases, and (5) extension of research time (if possible). From the research it was emphasized that the messages of Az-Zarnuji's educational concepts in the book Ta'limul Muta'alm; (1) good intentions to learn, (2) be grateful for what Allah has given, (3) focus and pursue knowledge, (4) may intend to seek knowledge with other intentions, (5) choose a teacher, (6) choose friends , (7) human nature, (8) trustworthiness, (9) memorization method, (10) causes of memory to be weak, (11) learning method, (12) time to study, and (13) worship.